An Atypical and Severe Case of Neuralgic Amyotrophy - Cadilha, Rui; Department of Physical and Rehabilitation Medicine, Centro Hospitalar São João, Porto (2017)
Neuralgic amyotrophy or Parsonage-Turner syndrome is an uncommon disorder, of unknown etiology, typically characterized by abrupt onset of shoulder and upper extremity pain followed by progressive neurologic deficits. An immune/autoimmune process seems to have more support in development of neuralgic amyotrophy. Neuralgic amyotrophy is a clinical diagnosis, however, further diagnostic studies can confirm clinical suspicion and help exclude other causes. The treatment consists predominantly in pain control and rehabilitation. Patients with neuralgic amyotrophy, can be evaluated by a wide range of clinical specialists in the early stage of disease before a correct diagnosis be made. This is a result of different phenotypes that this disorder exhibits, that complicate the diagnosis. It is important for clinicians to beware of the classic clinical manifestations that usually follow a characteristic clinical course of abrupt onset of shoulder girdle pain followed by progressive neurologic deficits as muscle weakness, amyotrophy and sensory abnormalities. We report the case of a 32-year-old man who had a severe bilateral and atypical shoulder involvement, that made the most probably diagnostic not so evident.